Negociações culturais em White Teeth (2000), de Zadie Smith - Rosado, Juliana Mara (2012)
The studies on literary productions have taken new parameters with the development of cultural studies which question the subjugation that the colonial heritage still submit some cultures nowadays. With regard to the portrait that literature offers to the reader about this veiled condition, the objective of this dissertation is to show the way in which the social relationship between different cultures are still permeated by inequalities when the "white" environment and the immigrants living in the English contemporary territory are compared. The presence of ethnic variety is analysed through theories such as Hall's (2003) on contemporary identity, on the colonial heritage studied by Gilroy (2001). Essential concepts from Ashcroft, Griffits and Tiffin (2000) foreground the development of many areas of multiculturalism as defined by Heckmann (1993), in which sociology texts and essays show, through literature, the effects of the presence of many and different cultures in the same country. The analysis of the novel is divided into specific studies of the three families, ranging from the identification of their singular characteristics and the way that they deal with the cultural aspects of the other cultures. The results indicate the maintenance of inequality relationships between the native "white" and the exogenous cultures. English superiority is constantly reaffirmed: the society which receives but fails to accept or recognize the value of the different ethnic people who which are also part of the English contemporary scene.